PENGARUH KARAKTERISTIK ORANGTUA DAN SEKOLAH TERHADAP TINGKAT KEPUASAN PELAYANAN PENDIDIKAN DASAR - Rahma, Atika; Hartoyo, Hartoyo (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2010)
School as an important role in human capital development. Therefore, school should perform good education services. The objective of this study is to analyze factors that influence parent’s satisfaction level of basic education services. This study used a cross sectional design and carried out at four Sub-Districts of Indramayu District. Samples of this study consist of 126 of elementary and secondary school students. The results of observation show that the condition of school facility included a medium category. Parents in elementary and secondary school in town and out of town felt satisfy toward basic education services, but parents in secondary school and town have more satisfied than in elementary school and out of town. Based on Importance and Performance Analysis (IPA), the attributes of education services that must repaired are student toilets, chair and desk, library, BOS fund and BOS fund of books. The attribute that must repair in particular at elementary school is information to parents about performance of their children, whereas attribute of blue uniform cost must repaired by secondary school. While special for secondary school in out of town that must repaired is maintenance of school building. Logistic regression analysis show factors that influence of parent satisfaction level (CSI indicator) are family size, father’s age, and school facility. While, family size, length of father education, valuation father toward education services, and CSI score influence parent satisfaction level (direct reported satisfaction).